Propuesta para la ejecución de una granja integral autosuficiente, que optimice la producción agropecuaria de la finca “Las Palmas” ubicada en el barrio La Chuva, parroquia San Roque perteneciente al cantón Piñas provincia de El Oro - Ramírez Criollo, Eddy Benigno (2016)
The Project of Thesis, Proposed for the execution of an Integral Self-sufficient Farm, which optimizes the Agricultural production of The Estate "Las Palmas", has as principal aim of elaborating an administrative and economic offer, for the implementation of an integral self-sufficient and profitable farm of the estate, to optimize the managing of the resources of the agricultural production of the same one and to treat of that he is a model for the majority of productive agricultural existing units in the way. Stimulating a culture of planning and structure of sustainable strategies in the sector, generating this way profitable UPAS in a harmonious environment between actors and his ecosystem. The techniques used in this study was the direct observation, interview and signingalso variables to assess used was to conduct a SWOT diagnosis, to know the strengths, weaknesses and the opportunities and Threats, as well as to apply the financial diagnosis, to know across the static and dynamic analysis his financial current position a financial plan to present identical future to his activities. Information that after being systematized, allowed to realize the future projection of the estate, taking in counts the best alternatives of development and the current reality of the same one, his possibilities of debt and profitability, improving and extending the production in the most priority fields, since it will be possible demonstrate in the different results of the work. The results demonstrate the need of changes in the productivity of the Estate, of an integral way, since there is verified that the income is not good, which podrís to get improved with improvements in his production. One concludes that the offer and execution of integral estates need a meticulous analysis of all the resources of the estate; hereby to project the actions that allow the integration and for ende better production. There is recommended the execution of this offer since it is focused on the reality of the Estate and in whose intentions were canalizing the different aspects in the managing of the productivity, which guarantees in the future his sustainability of an integral and efficient way.